Analysis of nicotine dependence among daily smokers in China: evidence from a cross-sectional study in Zhejiang Province - Yue Xu; Shuiyang Xu; QingQing Wu; Heni Chen; Dingming Yao; XiuJing Hu; Xuehai Zhang (BMJ Open, 2022)
Objective The current study aimed to assess the level of nicotine dependence and its influencing factors among daily smokers in Zhejiang, China.Setting The 2020 Global Adult Tobacco Survey was conducted in Zhejiang, China.Participants 1244 daily smokers aged ≥15 years.Measures Respondents were asked questions regarding their age, sex, residence, education level, occupation, household income, age of starting daily smoking and nicotine dependence.Results The findings revealed that 17.4% of daily smokers were highly dependent on nicotine, and the mean Fagerström Test for Nicotine Dependence score of daily smokers was (3.1±2.4). Age, educational level, occupation and age of starting daily smoking had significant effects on high nicotine dependence, whereas residence, sex and yearly household income were not significant factors. Compared with the age group ≥60 years, the proportion of respondents with a higher nicotine dependence level was lower in the age group of 15–39 years (OR=0.45). Daily smokers with a higher education level had a lower nicotine dependence level than those with a lower education level: primary or less (OR=3.07) and secondary (OR=2.62). Government institution staff (OR=4.02), unemployed persons (OR=3.08) and industrial workers (OR=2.46) had significantly higher nicotine dependence levels than did workers in the other occupation categories. People who started daily smoking at ≤18 years of age had a higher nicotine dependence level (OR=2.25) than those who started later.Conclusions This study elucidated that nearly one-fifth of daily smokers in Zhejiang, China, have high nicotine dependence levels. Improved health information on tobacco smoking is needed to encourage daily smokers to quit smoking, particularly among young males, unemployed persons and those with lower education levels.